Control System Design for a Ducted-Fan Unmanned Aerial Vehicle Using Linear Quadratic Tracker - Junho Jeong; Seungkeun Kim; Jinyoung Suk (International Journal of Aerospace Engineering)
Tracking control system based on linear quadratic (LQ) tracker is designed for a ducted-fan unmanned aerial vehicle (UAV) under full flight envelope including hover, transition, and cruise modes. To design the LQ tracker, a system matrix is augmented with a tracking error term. Then the control input can be calculated to solve a single Riccati equation, but the steady-state errors might still remain in this control system. In order to reduce the steady-state errors, a linear quadratic tracker with integrator (LQTI) is designed to add an integral term of tracking state in the state vector. Then the performance of the proposed controller is verified through waypoint navigation simulation under wind disturbance.